The Word Hunt Game as a Tool for Improving Vocabulary Mastery in EFL Learners - Elias Lasarus Kararbo; Doni Sudibyo (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
Vocabulary is a fundamental component of language proficiency that supports all aspects of communication. However, many junior high school students still face difficulties in mastering English vocabulary due to limited exposure, low motivation, and monotonous teaching methods. This study aimed to investigate the effectiveness of the Word Hunt Game in improving students’ vocabulary mastery among seventh-grade learners at SMP Negeri Persiapan Yenbeser. A pre-experimental quantitative design was employed using a one-group pre-test and post-test model. Twenty-five students participated in this study and received four sessions of Word Hunt Game activities designed to enhance vocabulary retention and engagement. The vocabulary test, consisting of 30 items, was administered before and after the treatment to measure improvement. Data were analyzed using descriptive statistics and a paired sample t-test. The findings revealed a significant increase in students’ vocabulary scores after the implementation of the Word Hunt Game. The mean score improved from 55.60 in the pre-test to 76.48 in the post-test, with a significance value of 0.000 (p < 0.05), indicating that the game had a substantial positive effect on students’ vocabulary mastery. The results suggest that the Word Hunt Game not only helps students memorize and recall new words more effectively but also increases their motivation and participation during learning activities. Therefore, it is recommended that English teachers incorporate game-based learning strategies like Word Hunt to make vocabulary instruction more interactive, enjoyable, and effective in EFL classrooms.